Case report: Transcatheter pulmonary valve-in-valve implantation in a deteriorated self-expandable valve caused by infective endocarditis - Li, Yan-Jie; Pan, Xin; Wang, Cheng; He, Ben (Frontiers in Cardiovascular Medicine, 2022)
Background: Infective endocarditis is a lethal complication in patients with congenital heart disease, particularly for those with bioprosthetic valve. Case summary: We report a case of a 54-year-old female with a history of tetralogy of Fallot surgically repaired using transannular patch had severe pulmonary insufficiency with right heart enlargement and presented with worsening dyspnea. She received transcatheter pulmonary valve implantation (TPVI) 5 years ago. Unfortunately, bioprosthesis-associated infective endocarditis occurred due to dental caries. By persistent antibiotic medication, she got clinical stable with prosthesis functional recovery. However, dysfunctional bioprosthesis was still detected, which was successfully treated by valve-in-valve TPVI with the help of modified buddy wire technique. At a 12-month follow-up, she was completely recovered with improved symptoms of heart failure. Conclusion: This is the first report of valve-in-valve TPVI of a self-expandable valve in a degenerated self-expandable valve. It highlights increased surveillance and suspicion for IE of transcatheter pulmonary valve should be emphasized. Subsequent valve-in-valve TPVI is an effective treatment for valve failure in defined conditions improving the hemodynamics.